Biomarcadores salivares do exercício físico para determinação do limiar anaeróbico humano - Bortolini Junior, Miguel Armando (2003)
The aim of this study was to evaluate the concentration of total salivary protein and compare it to the concentration of blood lactate during exercise with increased loads. Fifteen healthy non-smoking men underwent a maximal cycle ergometer test. The test started at 50 Watts (W), increasing from 50 by 50W to 200W, then increasing from 25 by 25W to exhaustion, lasting 3min per stage. Blood and saliva were collected at the end of each stage. The anaerobic lactate threshold (TA) is in accordance with the literature. Our results showed no significant differences (t-student test) and high Pearson correlations (p <0.05) of r = 0.95 for lactate compared to total salivary protein alone, divided by W or the mean heart rate (mFC - for thresholds expressed in W or mFC); for lactate divided by W or mFC compared to total salivary protein alone divided by W or mFC, r = 0.89 (for thresholds expressed in W) and r = 0.87 (for thresholds expressed in mFC). Therefore, it can be concluded that the anaerobic threshold of total salivary protein is strongly correlated with the blood lactate threshold and can be used as a new method to determine anaerobic threshold.